Over-coupled Helmholtz-like optical resonator for enhanced infrared spectroscopy of molecules - Paggi Laura; Fabas Alice; El Ouazzani Hasnaa; Fayard Nikos; Hugonin Jean-Paul; Bardou Nathalie; Dupuis Christophe; Greffet Jean-Jacques; Bouchon Patrick (EPJ Web of Conferences, 2023)
Electromagnetic Helmholtz resonators are able to strongly and homogeneously enhance an electric field in relatively large volumes, making them attractive for applications to surface enhanced infrared absorption spectroscopy of molecules. We show in this study that such a structure, designed in the over-coupling regime can demonstrate strong enhancement of molecular modes of the polymer poly(methyl methacrylate) and the explosive molecule 2,4-dinitrotoluene over a very wide wavelength range between 5 and 10 µm. Reflectivity contrast provides access to the analyte’s absorption and quantitative information. Helmholtz-like resonators therefore offer a new platform for the creation of sensitive and versatile sensors.